Adaptive guaranteed time slots allocation policy in wireless sensor networks with mobility awareness - LI Xiao-ji1; CHEN Chen1; QIU Hong-bing2; MO Wei2 (Tongxin xuebao)
To improve the connectivity in mobile wireless sensor networks,an adaptive GTS（guaranteed time slot） allocation algorithm with nodal mobility awareness was proposed.At first,the nodal location in next state was given by Kalman filters forecasting model.Then,a method that considered velocity,direction and relative mobility was used to define mobility level,based on which the nodal priorities for GTS reservation could be determined initially.Subsequently,the priorities could be adjusted adaptively according to the usage status feedback from allocated slots.Finally,the priorities could be used to determine the order for using GTS and the right of use an extra reservation slot.Simulation results show that the proposed scheme could increase the success rate of random access and ensure a lower average packets transmission delay and higher delivery ratio.Furthermore,with the adaptive adjustment scheme for reservation priorities base on usage feedback,the rate of correct utilization of allocated slots is increased significantly in the overall networks.